A Zinc(II) Porous Metal–Organic Framework and Its Morphologically Controlled Catalytic Properties in the Knoevenagel Condensation Reaction. Issue 9 (6th September 2017) - Wang, Jiajia; Wang, Xiaoxiao; Xu, Haitao; Zhao, Xi; Zheng, Zhizhong; Xu, Zhen‐liang
Abstract: A new metal–organic framework (MOF), {Zn(oba)(3‐bpdh)0.5 }∝ ⋅ 2 H2 O (1 Zn ; oba=4, 4′‐oxybis(benzoic acid), 3‐bpdh= N, N ′‐bis(1‐pyridine‐3‐yl‐ethylidene)hydrazine), was successfully assembled in a solvothermal system. The Zn 2+ ion center located in a five‐coordinate environment combined with oba to produce a layer‐like structure, which is again linked with 3‐bpdh to yield a 3D channel framework. MOF1 Zn microcrystals with different morphologies were synthesized through coordination modulation and solvent‐dependent methods. The effects of the concentration of the modulator, the reaction temperature, and the volume ratio of mixed solvents have been investigated. Furthermore, the catalytic performance in Knoevenagel condensation was studied for different morphologies of1 Zn microcrystals; this revealed that the MOF microcrystals exhibited excellent and morphology‐dependent catalytic properties. Abstract : Get in shape : Zinc metal–organic framework (MOF) microcrystals with different morphologies were synthesized through coordination modulation and solvent‐dependent methods and their catalytic performance in Knoevenagel condensation was studied (see figure). The catalytic properties of the MOF microcrystals is highly depended on the morphology.